2006
DOI: 10.1242/jeb.02489
|View full text |Cite
|
Sign up to set email alerts
|

Escape responses in juvenile Atlantic cod Gadus morhua L.: the effects of turbidity and predator speed

Abstract: SUMMARY We examined the effect of turbidity (0.5–14 beam attenuation m–1) and predator attack speed (150 and 296 cm s–1) on escape responses of juvenile cod Gadus morhua in the laboratory. We triggered escape responses using a predator model and measured escape timing, direction and locomotor performance. We also measured responsiveness and estimated the likelihood of fish escaping the`predator attack' (putative escape success, PES). Turbidity affected both PES and the type of esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 56 publications
8
62
0
Order By: Relevance
“…Domenici and Blake (Domenici and Blake, 1993) and Domenici and Batty (Domenici and Batty, 1997) found that mechanically stimulated single fish (herring Clupea harengus and angelfish Pterophyllum eimekei, respectively) tend to escape with peaks of ET 0 s at approximately 130 and 180deg (Fig.8A,E), which suggests that these two trajectories may correspond to either keeping the stimulus within the sensory discriminating zone or maximizing distance from the threat, respectively. Work using visual stimulation of fish shows a similar range of ET 0 s (Meager et al, 2006). Preferred ETs in a similar range to that found by Domenici and Blake (Domenici and Blake, 1993) are apparent in reanalysis of previous data sets (Eaton and Emberley, 1991;Walker et al, 2005) (Fig.8F,G, respectively).…”
Section: Fishsupporting
confidence: 81%
“…Domenici and Blake (Domenici and Blake, 1993) and Domenici and Batty (Domenici and Batty, 1997) found that mechanically stimulated single fish (herring Clupea harengus and angelfish Pterophyllum eimekei, respectively) tend to escape with peaks of ET 0 s at approximately 130 and 180deg (Fig.8A,E), which suggests that these two trajectories may correspond to either keeping the stimulus within the sensory discriminating zone or maximizing distance from the threat, respectively. Work using visual stimulation of fish shows a similar range of ET 0 s (Meager et al, 2006). Preferred ETs in a similar range to that found by Domenici and Blake (Domenici and Blake, 1993) are apparent in reanalysis of previous data sets (Eaton and Emberley, 1991;Walker et al, 2005) (Fig.8F,G, respectively).…”
Section: Fishsupporting
confidence: 81%
“…A fish that does not respond to an attack will most likely be eaten. Fuiman et al (2006) showed that responsiveness was the main factor affecting the vulnerability of red drum larvae, as it accounted for 86% of the variation in Meager et al (2006) Arrows indicate when the relationship implies an increase (m), a decrease(k), or no effect (2) on the escape component tested.…”
Section: Responsivenessmentioning
confidence: 99%
“…D 30 : the distance between the CM of the fish at the frame before the first visible response and 30 ms later (30 ms was chosen as a fixed time occurring during stage 2 in all individuals) (Meager et al, 2006).…”
Section: Definition Of Variablesmentioning
confidence: 99%